2021
DOI: 10.1177/01455613211066691
|View full text |Cite
|
Sign up to set email alerts
|

Association between olfactory dysfunction and COVID-19 severity: A prospective study in a highly complex hospital in Peru

Abstract: Introduction Olfactory dysfunction has been included among the early symptoms of coronavirus disease (COVID-19). Evidence suggests that a relationship exists between the duration of olfaction disorders and the probability of developing severe COVID-19. Given the scope of the COVID-19 pandemic, this study aimed to determine the frequency of smell alteration and its association with the severity of COVID-19 in a referral hospital in Peru, which is one of the most affected countries in the Latin American region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…On the other hand, several other studies [102][103][104][105] found no association between the OD and disease severity. This may purely be due to recall bias, where patients with severe COVID-19 may be less cognizant of OD due to the presence of more bothersome symptoms such as dyspnoea [4].…”
Section: Olfactory Dysfunction and Covid-19 Disease Coursementioning
confidence: 85%
“…On the other hand, several other studies [102][103][104][105] found no association between the OD and disease severity. This may purely be due to recall bias, where patients with severe COVID-19 may be less cognizant of OD due to the presence of more bothersome symptoms such as dyspnoea [4].…”
Section: Olfactory Dysfunction and Covid-19 Disease Coursementioning
confidence: 85%
“…21 Dalam beberapa penelitian, tidak ada perbedaan jenis kelamin yang memengaruhi fungsi penghidu selama infeksi COVID-19. 22 Pada dasarnya, kedua jenis kelamin menujukkan besarnya gangguan penghidu yang sama sebagaimana yang telah diukur oleh UPSIT. Hal ini menyatakan bahwa sejauh mana COVID-19 merusak sistem penghidu tidak bergantung pada jenis kelamin.…”
Section: Jenis Kelaminunclassified